2005
DOI: 10.1016/j.ijimpeng.2005.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of boundary conditions on the ballistic performance of high-strength fabric targets

Abstract: High-strength fabric is commonly used in personnel protection systems against small arms projectiles and fragments. An understanding of the characteristics of high-strength fabric under ballistic impact would provide useful insights for fabric armor design. A numerical model is formulated and used to study the perforation of square cross-woven fabric targets when the fabric is (i) clamped along all four edges with its yarns aligned parallel to the edges, (ii) clamped along all four edges with yarns running 451… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 9 publications
1
26
0
2
Order By: Relevance
“…Such slipping would be most significant for targets tested near their ballistic limit, when boundary conditions exert the most influence on the test results. Note that the effect of target slipping would be to extract energy from the projectile; neglecting this effect would tend to overestimate residual velocities for the thickest targets [36]. This possibility is consistent with an observed trend in the simulations, and it is independent of the material (neat or STF) type.…”
Section: Discussionsupporting
confidence: 80%
“…Such slipping would be most significant for targets tested near their ballistic limit, when boundary conditions exert the most influence on the test results. Note that the effect of target slipping would be to extract energy from the projectile; neglecting this effect would tend to overestimate residual velocities for the thickest targets [36]. This possibility is consistent with an observed trend in the simulations, and it is independent of the material (neat or STF) type.…”
Section: Discussionsupporting
confidence: 80%
“…The ballistic response of high-performance fabrics has been a topic of extensive research over the past three decades, which include analytical studies [1e6], experimental investigations [7e12] and numerical simulation [8,13e20]; comprehensive reviews have been presented by Cheeseman and Bogetti [21] and Tabiei and Nilakantan [22]. Results show that the impact resistance of these fabrics is influenced by a number of parameters, including material properties of the constituent fibre [13,22], fabric structure [7,12], projectile geometry [10,11], impact velocity [14,23], boundary conditions [7,8,24,25] and friction [12,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Cunniff (1992), Walsh et al (1998), Shim et al (1995), and Zeng et al (2005), among others, also observed slip of the fabric in experiments. The fabric slipped a maximum of 2-5 mm of from each side of the frame, during both the square and circular cut-out tests.…”
Section: Procedures For Low Velocity Projectile Impact (Arl) Experimentsmentioning
confidence: 68%